Tinjauan Potensi Fasilitas Daya Tarik Wisata Lubuk Paraku Kecamatan Lubuk Kilangan Kota Padang - Rani Aprilya Putri; Trisna Putra; Arif Adrian (Departemen Pariwisata Universitas Negeri Padang, 2023)
The background of this research is due to the lack of optimal development of the tourist attraction of Lubuk Paraku, Lubuk Kilangan District, Padang City. Lubuk Paraku has less potential to be developed in terms of the 4A tourist attraction indicators, namely Accessibility, Attraction, Amenities, Ancillary Service. This study describes the things that explain how the potential for tourist attraction in Lubuk Paraku, Lubuk Kilangan District, Padang City is based on the potential tourist attractions in Lubuk Paraku.This study uses a descriptive method with qualitative data, and uses a survey method. The data obtained were obtained from interviews, observation, and documentation. In conducting this research, the researchers involved 5 people who became informants in the study consisting of 2 Lubuk Paraku tourism managers, 1 local community member, and 2 visitors from the Lubuk Paraku tourist attraction. Researchers used purposive sampling techniques in conducting research and data analysis was carried out by means of reduction, presentation of data and drawing conclusions. Based on the results of this study, it can be concluded that the tourist attraction of Lubuk Paraku, Lubuk Kilangan District, has the potential to be developed in terms of attractions, such as natural tourist attractions and cultural tourist attractions as well as water and tropical forest tourist attractions along rivers, accessibilities such as access to get to Lubuk Paraku tourist attraction, Amenities such as existing facilities and facilities that can be developed, and Ancillary Services such as additional services and services for visitors while in Lubuk Paraku tourist attraction. With the development of Lubuk Paraku Tourism Attraction, it is hoped that it can have a good and positive impact on the world of tourism, especially in the city of Padang.